COMPETITIVE ADVANTAGE IN THE COMPANY - Dian Novita; Nurul Husna (TECHNOBIZ : International Journal of Business, 2020)
Competitive advantage is one of the aims pursued by most corporation in order to sustain in the business. Once the company could achieve a competitive advantage, it can increase the value and enhance the performance of the company. Competitive advantage is one of the aims pursued by most corporation in order to sustain in the business. Once the company could achieve a competitive advantage, it can increase the value and enhance the performance of the company. The purposes of this research are firstly is to analyze the concept of competitive advantages in orderly and secondly it is to analyzed the benefit of competitive advantages for the company. The method of this study is content analysis. This research is different from the previous one, it is present the competitive advantages in orderly, that has never been researched in advance and especially investigating competitive advantages. This paper result some propositions related to the competitive advantages concept. From this this research we can conclude the three things firstly, competitive advantages are rooted in superiority in performance, finance, and market positioning. And secondly, competitive advantages can create an added value for a company. Thirdly, competitive advantages suggest the meaning of the company’s having an excellent position relative to its competitors. The drawback of this research is incompleteness of the definition of competitive advantages which occurs every year